Investigating the factors of committing crimes using fuzzy TOPSIS / Norwaziah Mahmud ... [et al.] - Mahmud, Norwaziah; Jamaluddin, Siti Hafawati; Omar, Nur Azarina; Muhammat Pazil, Nur Syuhada (UiTM Cawangan Perlis, 2018)
It is a major concern for everyone when crime activities are on the rise particularly, if the crimes are happening near them. There is still lack of findings and understanding on the reasons for the occurrence of crimes albeit all the hue and cry. This study is to investigate the significant factors of committing crimes and also their respective ranking. The method of Fuzzy Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) was applied in this study. Fuzzy TOPSIS is commonly used for ranking purpose and selecting multi-criteria variables. Hence, this method is remarkably successful in determining the ranking of the factors as it relates to different criteria and alternatives. In this study, three decision makers are required to evaluate the factors using linguistic variables which vary from ‘very poor’ to ‘very good’. After applying fuzzy TOPSIS, the factors are ranked, thus the results show that lack of education is the major factor that contributes to crime behaviour with closeness coefficient value of 0.4661. The least contributing factor with closeness coefficient value of 0.3632 comes from poverty. The results of this study may be worthwhile for many personnel. Future research may expand the work with different types of criteria and alternatives.